2020
DOI: 10.1016/j.crfs.2019.11.004
|View full text |Cite|
|
Sign up to set email alerts
|

Inactivation of Salmonella enterica on post-harvest cantaloupe and lettuce by a lytic bacteriophage cocktail

Abstract: Salmonella enterica ( S. enterica ) is a causative agent of multiple outbreaks of foodborne illness associated with fresh produce, including pre-cut melon and leafy vegetables. Current industrial antimicrobial interventions have been shown to reduce microbial populations by <90%. Consequently, bacteriophages have been suggested as an alternative to chemical sanitizers. Seven S. enterica strains from four serovars (10 5 CFU/mL) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Similar to previous studies on phage-based biocontrol, bacterial regrowth was also observed during bacteriolytic experiment, likely due to the emergence of bacterial resistance mechanisms, including restricted modification systems, spontaneous mutations, and adaptive immunity through the CRISPR-Cas system (Oechslin, 2018). Several solutions have been proposed to delay bacterial regeneration, such as the use of high concentrations of phage suspensions (Guenther et al, 2009) and the use of phage cocktails or phages in combination with other antibacterial agents to minimize the impact (Abhisingha et al, 2020;Alves et al, 2020;Wong et al, 2020). In practice, food is naturally contaminated with a very low pathogen titer (Zhu et al, 2014).…”
Section: Discussionsupporting
confidence: 67%
“…Similar to previous studies on phage-based biocontrol, bacterial regrowth was also observed during bacteriolytic experiment, likely due to the emergence of bacterial resistance mechanisms, including restricted modification systems, spontaneous mutations, and adaptive immunity through the CRISPR-Cas system (Oechslin, 2018). Several solutions have been proposed to delay bacterial regeneration, such as the use of high concentrations of phage suspensions (Guenther et al, 2009) and the use of phage cocktails or phages in combination with other antibacterial agents to minimize the impact (Abhisingha et al, 2020;Alves et al, 2020;Wong et al, 2020). In practice, food is naturally contaminated with a very low pathogen titer (Zhu et al, 2014).…”
Section: Discussionsupporting
confidence: 67%
“…Phylogenetic analysis and sequence similarity searches revealed the phage vB_SenM-1 genome to be similar to previously described phage SE13. This phage has been characterized as being of broad host range among various S. enterica serotypes as well as having been effectively used as part of an experimental phage cocktail against Salmonella infection in food, especially cantaloupe and lettuce [ 34 , 46 ]. Moreover, phage LSE7621, to which phage vB_SenM-1 shows ~95% identity, has also been effectively tested in S. Enteritidis biocontrol on lettuce.…”
Section: Discussionmentioning
confidence: 99%
“…The combination treatment reduced bacteria by 3 log, but was less effective when seeds had been stored for 4 weeks or longer [21]. Most recently, her group is conducting a series of research projects exploring the use of bacteriophages (i.e., viruses that infect bacteria) on inactivating foodborne pathogens on fresh produce and poultry products [22]. This group works on improving food processing and safe food handling for long term food security.…”
Section: Novel Approachesmentioning
confidence: 99%